Differences in situation efficacy indicators at the elite basketball players that play on different positions in the team - Sindik, J.; Jukic, I. (Collegium Antropologicum, 2011)
The aim of our study was to determine the differences in situational efficacy for basketball players, in relation to their team positions: between guards and forwards/centres, and between the players on the four major positions in the team. The final sample of subjects (74 basketball players) is selected from the initial sample of 107 subjects, selected from nine men`s senior basketball teams that played in A-1 Croatian men`s basketball league championship in 2006/2007. Results confirmed the hypothesis that there is a significant difference between different groups of players: point/shooting guards, comparing with forwards/centres; players that play on four positions: point guard, shooting guard, small forward, power forward/centre. Guards have shown greater efficiency and utilization of the three-point shots, while centres are better in two-point shots. Guards have a greater number of assists, successful and unsuccessful three-point shots, while centres are better in the offensive and defensive rebounds, as same as in successful and unsuccessful two-point shots. No statistically significant differences were found among the players on the guard positions (point guard and shooting guard), while only one statistically significant difference is found among the players on the position forward/ centre (small forward and power forward/ centre).